ENERGY SECURITY IN THE INTERRELATIONS AMONG THE EU, RF, UKRAINE, AND CENTRAL ASIA - TOLSTOV, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2006)
In the last few years, energy transit and long-term energy supply issues have come to the fore on the international scene. The reasons are obvious: Europe and North America are consuming increasingly larger amounts of energy, while the prospect of oil, natural gas and, in the more distant future, coal (non-renewable energy sources) shortages loom all the more ominously. Everything related to international security (military security in particular) is highly structuralized within the system of international relations. However, Europe’s energy security, which is currently being discussed, has demonstrated a classic example of the inability of the state and corporate egotism to come to terms with each other in order to balance their highly varied interests. Seen as a possibility, disrupted energy supply and the resultant energy deficit as a whole have already created different behavior patterns in the energy suppliers and consumers. In the European context, successful agreements in this sphere are limited to bilateral contracts among the EU structure's, European energy distributors, and the energy supplier-companies, of which Russia’s Gazprom is the largest. More often than not the very complicated and fairly contradictory positions of the sides in-volved in the multisided process obscure the real content of the European energy security issue and delay long-term and mutually acceptable decisions. The newly formulated norms of obligatory and strict abidance by the rules of diversification and “free market” in the oil and gas trade have added to the political tension. Given the worst scenario, energy supply might develop into a sphere of bitter rivalry over short-term economic or political advantages. Political interests do not necessarily bring huge profits. In the European context, the compatibility of the EU’s and Russia’s long-term energy strategies remains the key issue of the related discussions. The Central Asian countries and Ukraine have an important, but relatively autonomous, role to play in the European energy balance. At the same time, the very fact that the energy security issue belongs to the power and influence context of international relations means that other inter-national political and economic actors intend to increase their presence in European oil and gas trade. The United States has its sights set on be-coming involved as one of the sides in oil and gas trade and transit contracts and agreements.